The End of a Stage (2011)
Santiago Velasquez, participant Expeditions to knowledge, speaks about his experience "This is my last year at the Children's University, because I graduate from school and want to dedicate myself to design and mechanics, that is why I chose philosophy: to experiment and see what it is like. It catches my eye a lot, because she's the mother of all sciences."